Analisis Metode Komunikasi SBAR di ruang Perawatan RSUD Otanaha Kota Gorontalo - Euis H. Hidayat; Riskawati Abuna (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
SBAR (Situation, Background, Assessment, & Recommendation) is a framework of communication techniques used between health service teams in communicating to convey patient conditions. SBAR is an effective form of communication that is used to avoid mistakes in managing actions on patients, preventing unexpected events and preventing injury to patients. the purpose of this study was to observe the SBAR communication method. This study used an observational and descriptive research design with an analytical approach to the SBAR communication method. With 12 nurses. This study uses data collection procedures by observing and documenting. Based on the results of the study, the average situational communication was 72.7%. Background communication obtained an average result of 79.15%. Assessment communication obtained an average result of 97.21%. Communication recommendations obtained an average result is 100%.